2020
DOI: 10.1101/2020.05.28.122143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogenetic clustering of the Indian SARS-CoV-2 genomes reveals the presence of distinct clades of viral haplotypes among states

Abstract: 21The first Indian cases of COVID-19 caused by SARS-Cov-2 were reported in February 29, 2020 22 with a history of travel from Wuhan, China and so far above 4500 deaths have been attributed to 23 this pandemic. The objectives of this study were to characterize Indian SARS-CoV-2 genome-24 wide nucleotide variations, trace ancestries using phylogenetic networks and correlate state-wise 25 distribution of viral haplotypes with differences in mortality rates. A total of 305 whole genome 26 sequences from 19 Indian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, the authors suggested that the strain is similar to those strains from Singapore and Philippines [ 54 ]. Furthermore, another study reported that isolate RK100 clustered with the ancestral first isolates from India that were originally reported from Kerala [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the authors suggested that the strain is similar to those strains from Singapore and Philippines [ 54 ]. Furthermore, another study reported that isolate RK100 clustered with the ancestral first isolates from India that were originally reported from Kerala [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…CoVs have the largest genomes (29.9-kilobase) among the known RNA viruses with several open reading frames (ORFs). 7 The two ORF (ORF1a/ORF1b) in combination contain two-thirds of the viral genome which directly encodes two polyproteins; namely, pp1a and pp1ab using host cell protein translation machinery. These polyproteins further processed into 16 non-structural proteins (nsps) by viral proteases enzymes like papain-like protease (PLpro) and 3C-like protease (3CLpro).…”
Section: Introductionmentioning
confidence: 99%
“…One aspect appears to be least concerned by healthcare professional is the past and ongoing evolution of the virus strain. Recent studies with a relatively limited number of samples for exploring the evolutionary history of SARS-CoV-2 have been restricted to either comparison with the possible ancestral forms (13,14) or a certain region and relatively smaller datasets (15)(16)(17)(18)(19). Here, a comprehensive dataset of 821 SARS-CoV-2 genomes from (13,14), was generated containing 16 non-structural proteins, four structural proteins and six accessory proteins (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%